Intra-cerebral haemorrhage but not neurodegenerative disease appears over-represented in deaths of Australian cadaveric pituitary hormone recipients. (November 2020) - Alnakhli, Sultan H.; Wand, Handan; Law, Matthew; Sarros, Shannon; Stehmann, Christiane; Senesi, Matteo; Klug, Genevieve M.; Simpson, Marion; Lewis, Victoria; Masters, Colin L.; Collins, Steven J.
Highlights: Transmission of non-prion disease causing deaths in cadaveric pituitary hormone recipients. Deaths from intra-cerebral haemorrhage, potentially related to cerebral amyloid angiopathy, were increased. Despite limitations, there was no evidence of increased non-prion neurodegeneration-related deaths. Abstract: Background and purpose: Recent scientific reports and epidemiological studies have engendered mounting concerns regarding the potential human-to-human transmissibility of non-prion neurodegenerative and related diseases. This study investigated whether recipients of cadaveric pituitary hormone treatments are at increased risk of death from non-prion neurodegenerative and related diseases. Methods: A retrospective national cohort study based on death certificates of recipients of the cadaveric pituitary hormone treatments (n = 184) as part of the Australian Human Pituitary Hormone Program (AHPHP; n = 2940) 1967–1985. Standardised mortality ratios (SMR) from non-prion neurodegenerative and other diseases were estimated based on the Australian population. Results: Allowing for potential diagnostic mis-attributions, there was no significant increase in the SMR from non-prion central nervous system (CNS) neurodegenerative disease, especially dementia and/or Alzheimer's disease (0.47; [95% CI: 0.19, 1.12] P = 0.081). The SMR for intra-cerebral haemorrhage, potentially related to cerebral amyloid angiopathy (CAA), was increased (2.77; [95% CI: 1.12–5.75] P = 0.009), although accommodation of possible mis-diagnosis through conflation of this category with other stroke causes of death emphasising likely intra-cranial haemorrhage showed no persisting significant increase in mortality in cadaveric pituitary hormone recipients, including all deaths recorded as due to intra-cranial haemorrhage (1.72; [95% CI: 0.80, 3.26] P = 0.123). Conclusion: In the setting of recent evidence strongly supporting the likelihood of brain-to-brain horizontal transmission and subsequent propagation and deposition of abnormally folded proteins associated with non-prion neurodegenerative and related disorders, this study offers further tentative support for deaths directly stemming from transmission of non-prion disease related to cadaveric pituitary hormone treatment. Acknowledging the limitations of the present study, however, ongoing detailed assessments of this potential risk are necessary.